150 A Factorial Approach to Estimate Energy Requirements and Feeding Levels for Boars in Studs. (7th May 2021) - Lu, Ning; Kleve-Feld, Michael; Wilson, Mark E; Vier, Carine M; Cast, Wayne R; Navales, Ron A; Dritz, Steve S; Orlando, Uislei A
Abstract: Boars are a source of genetic improvement and influence farrowing rate and litter size. Overfeeding boars increases incidence of feet and leg problems and reduces libido, whereas underfeeding boars may decrease semen output and libido. To help boar stud personnel estimate the energy requirements and base feeding levels, an interactive web application named PIC Optimum Boar Feeding Tool has been developed. The application encompasses three components, including an input interface using dynamic models to estimate energy requirement, an output interface displaying recommended feeding program, and functional modules facilitating the ease of use. The input interface requests users to provide the start and final weight of boars in isolation, isolation length, boar stud room temperature, number of collections per week, and dietary energy level. The daily energy requirement (Mcal of ME/day) is calculated using the following energy-demanding factors: 1) maintenance, 0.1823 × (body weight, kg) 0.665 ; 2) weight gain, 0.00489 × (average daily gain, kg/d); 3) each degree below 17°C for individually penned boars on slatted floors, 0.00382 × (body weight, kg) 0.75 ; 4) mating activity, 0.0043 × (body weight, kg) 0.75 ; and 5) sperm production, 0.1. These factors and the user-defined inputs including dietary energy, are used to calculate a daily feeding amount. The users also have the option to calculate the recommended feeding level for boars of specified body weight. Other functional modules include a flank-to-flank measurement tool that estimates boar body weight and customized downloadable nutrient specifications. This web application incorporates a spectrum of biological, nutritional, and management aspects to allow boar stud personnel to easily make boar feeding decisions.